Pokazateli psichofiziologiceskogo sostojanija sportsmenov igrovikov v situacijach s razlicnoj psichoemocional'noj naprjažennost'ju - Lutkova, N. V.; Makarov, Yu. M.; Minkin, V. A.; Nikolaenko, Ya. N. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
It is common knowledge that in each game situation the athlete is under the specific psychophysiological state (PFS). Therefore, in diagnostics the prompt assessment of situational condition of the athlete, his psychophysiological reaction to game situations with different degree of psychoemotional tension is important. However, the focus only on obtaining the urgent information on PFS cannot be sufficient if the parameters under investigation do not meet the requirements of the information content, and reliability. The analysis of psychophysiological states of the athletes shows that in game situations with different psychoemotional tensions the indicators characterizing the state of aggressiveness, self-regulation, energy and charismatic change. The presented parameters of the single indicators of PFS are absolutely legitimate as objective criterion in assessment of influence of the game situations with different psychoemotional tension on body of the athletes. These conditions need to be known, studied and predicted in conditions of training and competitive activity. Vibration imaging technology is the most attractive method for urgent diagnostics of PFS.